2014
DOI: 10.1016/j.febslet.2014.02.054
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐145, miR‐133a and miR‐133b inhibit proliferation, migration, invasion and cell cycle progression via targeting transcription factor Sp1 in gastric cancer

Abstract: Edited by Tamas Dalmay Keywords:Gastric cancer miR-145 miR-133a miR-133b Proliferation Migration Invasion Cell cycle progression Sp1 a b s t r a c t MicroRNAs have recently emerged as key regulators of gastric cancers. Here we found that miR-145, miR-133a and miR-133b were down-regulated in gastric cancer tissues and cell lines. Overexpression of miR-145, miR-133a and miR-133b induced G1 cell cycle arrest and inhibited cell proliferation, migration and invasion in vitro. MiR-145, miR-133a and miR-133b targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
125
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 46 publications
12
125
0
1
Order By: Relevance
“…miR-29b and miR-375 function as tumor suppressors in TSCC through targeting SP1 (39,40). miR-145, miR-133a, miR-133b, miR-22 and miR-335 serve an important role in the biology of gastric cancer by regulating SP1 directly (41)(42)(43). miR-145 was also found to regulate SP1 in ovarian cancer cells sensitized to paclitaxel (44).…”
Section: Discussionmentioning
confidence: 95%
“…miR-29b and miR-375 function as tumor suppressors in TSCC through targeting SP1 (39,40). miR-145, miR-133a, miR-133b, miR-22 and miR-335 serve an important role in the biology of gastric cancer by regulating SP1 directly (41)(42)(43). miR-145 was also found to regulate SP1 in ovarian cancer cells sensitized to paclitaxel (44).…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest that the antitumor effect of propofol on pancreatic cancer cells may be partly due to the upregulation of miR-133a. miR-133a downregulation has been confirmed in lung cancer (Moriya et al, 2012), breast cancer (Wu et al, 2012), rhabdomyosarcoma (Missiaglia et al, 2010), maxillary sinus squamous cell carcinoma (Nohata et al, 2011), tongue cancer (Wong et al, 2008), esophageal cancer (Kano et al, 2010), gastric cancer (Qiu et al, 2014), prostate cancer (Kojima et al, 2012), ovarian cancer (Guo et al, 2014), renal cell carcinoma , and pancreatic cancer (Qin et al, 2013). In these cancers, decreased miR-133a expression results in the induction of cell proliferation, the inhibition of apoptosis, or the promotion of cell invasion, indicating that miR-133a acts as a tumor-suppressor miRNA.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Qiu et al. 27 stated that miR‐145, miR‐133a, and miR‐133b could inhibit proliferation, migration, invasion, and cell cycle progression of gastric cancer cells by regulating transcription factor Sp1. More recently, studies showed miR‐133b may affect the response of chemotherapy in certain cancer.…”
Section: Discussionmentioning
confidence: 99%